The action research dissertation a guide for students and faculty - Herr, Kathryn; Anderson, Gary L. 1948- (SAGE Publications, Inc., 2015)
The first edition of this book was a first-of-its-kind reference, distilling the authors’ decades of action research experience into a handy guide for graduate students. The Second Edition continues to provide an accessible roadmap that honors the complexity of action research, while providing an overview of how action research is defined, its traditions and history, and the rationale for using it. The authors demonstrate that action research is not only appropriate for a dissertation, but also is a deeply rewarding experience for both the researcher and participants. This practical book demonstrates how action research dissertations are different from more traditional dissertations and prepares students and their committees for the unique dilemmas they may face, such as validity, positionality, design, write-up, ethics, and dissertation defense. Quelle/Source: Klappentext.